An endeavor to improve longevity of cryopreserved equine sperm - KCHALIFA, TAA; WAHEED, M. M.; LYMBEROPOULOS (Α.Γ. ΛΥΜΠΕΡΟΠΟΥΛΟΣ), A. G. (Journal of the Hellenic Veterinary Medical Society, 2017)
Exposure of sperm cells to the oxidative stress pending hypothermic storage of semen has been suggested to be responsible, in part, for the decline of their motility and fertility. This study was conducted to evaluate the in-vitro effects of antioxidants (AOs) and / or caffeine on longevity of cryopreserved stallion spermatozoa. Aliquots from the gel-free fraction of semen ejaculates (n=12), collected from 5 Arabian stallions (9-18 years old) of unknown sperm freezability, were mixed 1:1 with a Tris-egg yolk extender (TEYE), centrifuged at 500 χ g for 5 min and sperm cells were frozen in the form of 0.25-ml concentrated pellets after 2-step addition of TEYE supplemented with or without AOs (0.50 mg /ml Na pyruvate, 1 mg / ml Na thiosulfate, 5 mg / ml bovine serum albumin, 0.15 mg / ml zinc chloride and 0.50 mg / ml ferulic acid). The final pre-freeze concentrations of glycerol and sperm cells were 5% and 562-924 χ IO6 / ml, respectively. Frozen pellets from non-AOs and AOs-treated sperm were thawed in a Tris-citric acidglucose solution (40°C) containing 0, 0.49, 0.97 or 1.94 mg / ml caffeine and incubated (140-230 χ IO6 sperm / ml) at 30°C for 3 h. Sperm progressive motility (%) was assessed after centrifugation, before freezing and after 0, 1, 2 and 3 h of thawing. The results revealed significant (P<0.05) effects of sperm treatments only on post-thaw motility. Neither AOs alone nor caffeine alone could significantly ameliorate the maintenance of sperm motility. AOs plus 0.97 or 1.94 mg / ml caffeine were the superior supplements in improving the longevity of stallion spermatozoa.